Transmission Expansion Planning With Wind Power Plant Using Differential Evolution Algorithm - Shilaja C (International Journal of Advanced Science and Technology, 2020)
Nowadays modern electric power systems consist of large-scale and highly complex interconnected transmission systems, thus transmission expansion planning (TEP) is now a significant power system optimization problem. The TEP problem is a large-scale, complex and nonlinear combinatorial problem of mixed integer nature where the number of candidate solutions to be evaluated increases exponentially with system size. In recent years differential evolution algorithm (DE) procedures have been attracting significant attention from the researchers as such procedures have been found to be extremely effective in solving power system optimization problems. In this paper, the TEP problem has been investigated in static form. In addition, one cases of the static TEP problem, without generation resizing, have also been investigated. The proposed method has achieved solutions with good accuracy, simple implementation and satisfactory computation time. The analyses have been performed within the mathematical programming environment of MATLAB using DE a detailed comparison has also been presented.